(untitled) (Gaceta Técnica, 2019)
This paper is about the experimental determination of the active lateral pressure distribution of a granular soil on a rigid retaining wall undergoing a horizontal translation and a rotation about the top. The pressure measurement was made using load cells as sensors, being the variables the relative density of the backfill and the rugosity of the wall backside. The placement of backfill in loose and dense state was obtained by using the pluviation and the mesh extraction methods, respectively. The wall movement was controlled by a simple mechanical system. The experimental results obtained lead to the general conclusion that loose soils show a linear distribution, and dense soils, a non-linear distribution. Particularly, the distribution of the lateral pressure of a dense backfill against wall that moves horizontally and rotates about the top, shows two peaks. This fact is explained by the Granular Mechanics as the juxtaposition of two pressure distributions related to horizontal translation and rotation about the top